Hurricanes have eyes but can't see : and other amazing facts about wild weather - Berger, Melvin; Berger, Gilda (New York : Scholastic Inc., 2003)
Weather can be wild. Thunderstorms, hurricanes, tornadoes, and other storms can cause accidents, damage property, and injure people. Learn about what makes wild weather and what you can do to keep safe.
Introduction -- Thunderstorms -- Monsoons -- Hurricanes -- Tornadoes -- Blizzards -- Rainstorms -- Ice storms -- Droughts -- Dust storms -- Hailstorms -- Fog -- Heat waves -- Forecasting wild weather.
Keywords: Storms -- Juvenile literature; Tornadoes; Hurricanes; Questions and answers; Blizzards; Weather; Meteorology; Literature